exploring Exploring Opinion Exchange in Speaking Learning through Task-Based Language Teaching: A Case Study at Senior High School: Introduction Importance of Speaking Skills in EFL Learning Challenges in Speaking Activities Role of Task-Based Language Teaching (TBLT) The Influence of Gender on Participation and Interaction Research Methodology Research Design and Approach Participants and Location Data Collection Procedures and Learning Design Data Collection Instruments Findings and Discussion - Hanif Abdulah Riyadi; Kusrin; Sumarta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore how Opinion Gap Tasks in the Task-Based Language Teaching (TBLT) framework facilitate students' speaking skills development through opinion exchange activities and analyze how gender differences influence students' participation, interaction patterns, and performance during these tasks. A qualitative case study design was employed, involving 11th-grade students from a high school in Lembang. Data were collected through classroom observations and semi-structured interviews, and analyzed using Braun and Clarke's (2006) Thematic Analysis and Toulmin's (1958) Argumentation Model. The findings reveal different communication and reasoning patterns between male and female students. Female students were more expressive, emotional, and confident, often relying on experiential reasoning and empathy, while male students were more logical, structured, and cautious in their argumentation. Despite these differences, both genders found Opinion Gap Tasks effective in enhancing fluency, confidence, and critical thinking in speaking English. These tasks also fostered respect for differing opinions, learner autonomy, and reflective awareness in communication. Overall, the study concludes that integrating Opinion Gap Tasks into TBLT effectively promotes inclusive communicative competence and meaningful language learning in the EFL classroom. Keywords: Task-Based Language Teaching, Opinion Gap Tasks, Opinion Exchange, Gender, Speaking Skills.